Lithium management of periodic mood fluctuations in behavioural frontotemporal dementia: a case report - Llorca-Bofí, Vicent; Batalla, Iolanda; Ruiz-Julián, Maria; Adrados-Pérez, Marina; Buil-Reiné, Esther; Piñol-Ripoll, Gerard; Gallart-Palau, Xavier; Torrent, Aurora (Frontiers in Psychiatry, 2024)
The behavioral variant of Frontotemporal dementia (bvFTD) is a neurodegenerative condition characterized by behavioral and cognitive symptoms. Mood disturbances, including manic-like episodes, can occur in bvFTD, posing diagnostic and therapeutic challenges. This case report presents a 62-year-old male with bvFTD exhibiting weekly mood fluctuations alternating between manic and depressive-like states. While initial treatment with quetiapine and trazodone showed partial improvement, the periodicity of mood fluctuations persisted. Subsequently, lithium was introduced, resulting in a notable reduction in symptom severity for both manic and depressive episodes. This report highlights the potential use of lithium as a mood stabilizer in bvFTD patients with periodic mood fluctuations, refractory to standard treatments. Further research is needed to elucidate the mechanisms underlying lithium's efficacy in bvFTD and to establish treatment guidelines.